Fertility Outcome of Vasectomy Recanalization: A Review (Journal of Rangpur Medical College, 2023)
Non Scalpel Vasectomy (NSV) is used extensively for male sterilization by the family planning industry in Bangladesh. But if NSV needs a reverse procedure (recanalization), variable rates are observed in different studies. We collected articles from Hinari, Pubmed and Banglajol with extensive searches. We compared these results between articles and recommended the best vasectomy reversal (NSV) procedure for male clients.J Rang Med Col. March 2023; Vol. 8, No. 1:69-71